Pendidikan Humanis dalam Film Upin Ipin Episode Lebaran Idul Fitri - Indah Novita Sary; Asnawi Asnawi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Humanist education is a human's understanding of the environment and oneself, a unique, autonomous and creative human system, determining each person's behavior. One way to implement the idea of ​​humanist education is through the use of animated films, one of which is the animated film Upin Ipin episode of Lebaran Idul Fitri. The animated film Upin Ipin shows how peaceful multiculturalism is, the film shows how multicultural communities can live side by side happily even though they come from different cultural origins. The aim of this research is to identify and describe the values ​​of humanist education contained in the film Upin and Ipin episode Riang Raya. This research uses a qualitative descriptive approach. The source of research data is the Upin Ipin film Eid Al-Fitr episode which is available on YouTube. Data collection techniques are by listening, recording and taking notes. Data analysis in this research uses content analysis. The results of this research show that the Upin Ipin animated films episodes Riang Raya, Raya Full of Meaning and Ragam Raya contain humanist educational values, namely democracy, pluralism, humanity, religion, freedom, tolerance and justice. The Upin Ipin film can be used as a teaching medium for humanist education.